Sustainable soil health management through site specific nutrient management in rice using nutrient expert in Bihar - SHAHI, V. B.; MAJUMDAR, KAUSHIK; DUTTA, S.; KOHLI, ANSHUMAN (Journal of Soil and Water Conservation, 2017)
Nutrient Expert (NE) was evaluated in Bihar comparing results against the State Recommendations (SR) and Farmersâ€™ Fertilizer Practice (FFP). NE determines field-specific fertilizer rates for nitrogen, phosphorus, and potassium requirements for cereal crops. We used recent advances in information and communication technology and computer base applications of â€œNE for rice, wheat and maizeâ€ which transforms the science of SSNM into field- specific needs and conditions of a farmer. Across all sites, NE Rice increased yield and economic benefit over FFP and SR. Compared with FFP, it increased average yield by 0.54 t/ha with decrease in fertilizer N (-34.2 kg N/ha) and P (-16.4 kg P2O5/ha) but with large increase in fertilizer K (+37 kg K2O/ha). Recommendations from NE Rice also increased yield (by 0.41 t/ ha) over SR with moderate increase in fertilizer K (+11.5 kg K2O/ha) and N and P fertilizer was decrease N (-12.5 kg N/ha) and P (-29.8 Kg P2O5/ha). Thus, NE based fertilizer application resulted in significantly higher grain yields over farmer fertilizer practice (FFP) and State recommendation (SR). Average rice yield with NE based fertilizer recommendation was 4.06 t ha-1, which was 11.61% more than the SR and 15.84% higher than the FFP. With NE an additional net income of Rs. 6200 ha-1 and Rs. 7798 ha-1 was obtained over SR and FFP, respectively.